Foreign direct investment and productivity growth in Eastern European countries - Ozcan Karahan; Olcay Colak (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: Our study aims to investigate the technological spillover effects of Foreign Direct Investment flows to Eastern European Countries. This study has guided by new growth theories arguing that Foreign Direct Investment has a significant potential for improving the productivity growth rate of host countries through technology transfer. Design/methodology/approach: The impact of potential spillover effects associated with FDI flows on productivity growth has been examined by constructing the baseline specification of which Gersl et al. (2007) and Stancik (2009) based on Cobb-Douglas type production function. Through the baseline model, we performing conventional linear panel data models namely the fixed effect and random effect. For the robustness of the empirical findings, we also employ a dynamic panel data estimator in the framework of the GMM technique. Findings: Results based on the fixed effect estimator show that there are no horizontal and forward spillovers while positive backward spillovers prevail in both manufacturing and services sectors, that is also confirmed by the findings of the dynamic panel data (GMM) estimator. Research limitations/implications: Our findings regarding the presence of positive backward spillovers versus the absence of horizontal and forward spillovers are consistent with the results of most empirical studies dealing with Eastern European Countries. However, our study has also revealed that these results do not differ between the manufacturing and service sectors in Eastern European Countries. Originality/value: In the literature focusing on Eastern European Countries, many studies investigate the presence of the spillover effect by not making a distinction between the manufacturing and services sectors. Our study is one of the first to examine how spillovers from FDI affect domestic firms in two different sectors namely manufacturing and services. Thus, this study contributes to related literature by showing whether the spillovers from FDI exist differently in the manufacturing and services sector or not.
Keywords: F21; F23; D24; O52; 330; Foreign Direct Investment; Productivity Growth; Eastern European Country